Working Memory is Associated with Distributed Executive Control Networks in Schizophrenia - Wylie, Korey P. (J Neuropsychiatry Clin Neurosci, 2019)
Working memory impairments represent a core cognitive deficit in schizophrenia, predictive of patients’ daily functioning, and one that is unaffected by current treatments. To address this, working memory is included in the MATRICS Consensus Cognitive Battery (MCCB), a standardized cognitive battery designed to facilitate drug development targeting cognitive symptoms. The neurobiology underlying these deficits in MCCB working memory is currently unknown, however, mirroring the poor understanding of working memory deficits in general in schizophrenia. To investigate this neurobiology, 28 subjects with schizophrenia were administered working memory tests from the MATRICS Consensus Cognitive Battery (MCCB) and examined with resting state fMRI. Intrinsic Connectivity Networks were estimated with Independent Components Analysis. Every voxel’s time series was correlated with each network time series, creating a feature vector for voxel-level connectivity analysis. This feature vector was associated with working memory using the Distance Covariance statistic. Results demonstrated that the neurobiology of MCCB working memory tests largely follows the multi-component model of working memory, but revealed unexpected differences. The dorsolateral prefrontal cortex was not associated with working memory. The Central Executive system was instead associated with delocalized Right and Left Executive Control Networks. The Phonologic Loop within the multicomponent model, a subsystem involved in storing linguistic information, was associated with connectivity to the left temporoparietal junction and inferior frontal gyrus. However, connections to the Language Network did not predict working memory test performance. These results provide supporting evidence for the multi-component model of working memory in terms of the biology underlying the MCCB.